Dapagliflozin Protects Methamphetamine-Induced Cardiomyopathy by Alleviating Mitochondrial Damage and Reducing Cardiac Function Decline in a Mouse Model - Shanqing He; Shanqing He; Shanqing He; Yajun Yao; Yajun Yao; Yajun Yao; Nan Yang; Youcheng Wang; Youcheng Wang; Youcheng Wang; Dishiwen Liu; Dishiwen Liu; et al. (Frontiers Media S.A., 2022)
Background: Methamphetamine (METH)-induced cardiovascular toxicity has been attributed to its destructive effect on mitochondrial function at least to some extent. Previous studies highlighted the benefits of dapagliflozin (DAPA) on the cardiovascular system, but the response of METH-induced cardiomyopathy to DAPA is never addressed before. The present study aimed to investigate the potential ability of DAPA in preventing METH-induced cardiomyopathy.Materials and Methods: C57BL/6 mice were randomly divided into control group (n = 24), METH group (n = 24), and METH + DAPA group (n = 24). The METH-induced cardiomyopathy group received intraperitoneal METH injections at gradually increasing doses thrice weekly for 14 weeks. Mice in the METH + DAPA group were simultaneously treated with DAPA 1 mg/kg/day by intragastric administration. Echocardiography was performed to assess cardiac function. Reactive oxygen species (ROS), JC-1, and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assays were performed to evaluate oxidative stress, mitochondrial damage, and apoptosis, respectively. Mitochondrial and apoptosis-related protein expression was measured by western blotting.Results: Mice exposed to METH exhibited reduced cardiac function (left ventricular ejection fraction [LVEF]: 56.51 ± 6.49 vs. 73.62 ± 1.42, p < 0.01), fibrotic remodeling, and mitochondrial dysfunction, leading to apoptosis (apoptotic cells%: 7.4 ± 1.3 vs. 1.3 ± 0.5, p < 0.01). DAPA significantly reduced mitochondrial dynamics and function, ROS, apoptosis (apoptotic cells%: 2.4 ± 0.8 vs. 7.4 ± 1.3, p < 0.01), cardiac function decline (LVEF: 70.99 ± 4.936 vs. 56.51 ± 6.49, p < 0.01), and fibrotic remodeling. These results indicated that DAPA could be considered as an effective therapeutic agent in the protection against METH-associated cardiomyopathy.Conclusion: DAPA protects against METH-induced cardiomyopathy in mice by decreasing mitochondrial damage and apoptosis.